Typologia polskich partii politycznych według kryterium programowego - Kowalczyk, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The author of the paper presents a typology of parliamentary parties in Poland on the basis of what he deems to be the key element when establishing a party, namely its political platform. He outlines social-democratic, liberal, Christian-democratic, conservative, people’s parties, independence parties and the parties he terms as non-standard ones. He concludes by presenting a table with an interesting list of all the parliamentary parties from the first to the seventh term.
The typology of political parties in Poland made on the basis of their political platform